PENILAIAN LINGKUNGAN, BANGUNAN DAN FASILITAS SANITASI DI PASAR HEWAN BANGKAL SUMENEP - Ovie Lutfiyah Putri; Suparlan .; Imam Khambali (GEMA LINGKUNGAN KESEHATAN, 2014)
Sanitation is an effort to control factors of physical environment that may have impacts onhumans especially those having destructive effects toward physical, health and survival. A market is a placeof gathering and meeting between people to carry out their interactiion and business with each other. Thusit needs to be equipped with sanitary facilities and guidelines on the implementation of the principles ofhealthy market designated in the Health Ministerial Decree NO.519/MENKES/SKjVI/2008.The purpose of this study is to evaluate the environment, building and sanitation facility inBangkal animal market at Sumenep in 2014. This study is a descriptive study using cross sectionalapproach. Data colletion was done through observation, measurements, interviews and use ofquestionnaires.Results of this study showed that there were 3 variables which did not comply to the standardrequirements. They were: wastewater disposal with percentage of 50%, hygienic behavior of the tradersand visitors with 0% percentage, and provision of first aid box with 0% percentage.It is suggested that the sanitation facilities in Bangkal animal market Sumenep must beimmproved toward the guidelines of the operation of healthy market set forth in the Health MinisterialDecree NO.519/MENKES/SK/Vl/2008.